2005
DOI: 10.1200/jco.2005.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Results in Localized Primary Gastric Lymphoma: Data of Patients Registered Within the German Multicenter Study (GIT NHL 02/96)

Abstract: In this nonrandomized study (02/96), we reproduced the previous results of study 01/92 showing no disadvantage for an organ-preserving treatment. Therefore, primary stomach resection should be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
128
2
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(151 citation statements)
references
References 26 publications
10
128
2
10
Order By: Relevance
“…Indeed, PGL of MALT type, when confined to mucosa and sub-mucosa layers responds to HP eradication therapy without any need of chemotherapy, meanwhile DLBCL are usually treated as general disease with chemo-immuno-therapy, even if recent case reports indicated the regression of locally staged DLBCL after HP eradication (Montalban et al, 2001, Tari et al, 2009. Independently from the stage and dissemination, transformation to DLBCL occurs in about 10% of the cases (Zucca et al, 2008 The GIT NHL 02/96 study, confirming the results of the previous study GIT NHL 01/92, revealed that surgery is no longer the better strategy in early-stage low-and high-grade gastric lymphomas (Koch et al, 2005), except when perforation, bleeding or obstruction take place, proving these findings in a cohort of 363 patients. Firstly, the great impact of the stomach-preserving treatment has been suggested by Fischbach in a prospective nonrandomized trial, reporting a survival rate from 89% to 96% at 2 years for low-grade lymphomas and from 83% to 88% for high-grade lymphomas (Fischbach et al, 2000).…”
Section: Prognostic Assessment and Treatment: How Endoscopic Ultrasousupporting
confidence: 57%
“…Indeed, PGL of MALT type, when confined to mucosa and sub-mucosa layers responds to HP eradication therapy without any need of chemotherapy, meanwhile DLBCL are usually treated as general disease with chemo-immuno-therapy, even if recent case reports indicated the regression of locally staged DLBCL after HP eradication (Montalban et al, 2001, Tari et al, 2009. Independently from the stage and dissemination, transformation to DLBCL occurs in about 10% of the cases (Zucca et al, 2008 The GIT NHL 02/96 study, confirming the results of the previous study GIT NHL 01/92, revealed that surgery is no longer the better strategy in early-stage low-and high-grade gastric lymphomas (Koch et al, 2005), except when perforation, bleeding or obstruction take place, proving these findings in a cohort of 363 patients. Firstly, the great impact of the stomach-preserving treatment has been suggested by Fischbach in a prospective nonrandomized trial, reporting a survival rate from 89% to 96% at 2 years for low-grade lymphomas and from 83% to 88% for high-grade lymphomas (Fischbach et al, 2000).…”
Section: Prognostic Assessment and Treatment: How Endoscopic Ultrasousupporting
confidence: 57%
“…37,38 Isaacson 39 previously proposed a classification of primary gastrointestinal non-Hodgkin lymphoma that comprised cases of both low-grade and high-grade MALT; however, the current WHO lymphoma classification no longer uses such terminology, and cases of high-grade MALT have been subsumed into the large B-cell lymphoma category (Table 1). 37,40 GASTROINTESTINAL B-CELL LYMPHOMAS, PREDOMINATELY NON-MALT Most primary gastrointestinal lymphomas, both in stomach and intestine and irrespective of their association with MALT, are large B-cell lymphomas, especially those composed of centroblasts, but may also include cases dominated by immunoblasts and, on occasion, plasmablasts. The relationship between the more common large B-cell gastrointestinal lymphomas and the low-grade lymphomas of MALT is unclear.…”
Section: Classification Of Gastrointestinal Lymphomasmentioning
confidence: 99%
“…PGL is a unique disease and has a variety of pathological types, and DLBCL and MALT lymphoma account for the majority of PGLs (97.4%) (4,5). Hp infection is important in the development of PGL.…”
Section: Discussionmentioning
confidence: 99%
“…PGL is the most common extranodal lymphoma, representing 20-40% of all extranodal non-Hodgkin's lymphomas (2,3). Diffuse large B-cell lymphoma (DLBCL) accounts for the majority of PGL (59.5%), followed by the mucosa-associated lymphoid tissue (MALT) type (37.9%) (4,5).…”
Section: Introductionmentioning
confidence: 99%